(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This study proposes new approaches to body archives, inspired by the relational and presence-based perspectives of Lume Teatro and the concept of the open work (Campos, 1955; Eco, 1976). It considers contemporary forces such as cultural hybridization (Canclini, 2008) and the deconstruction of the individual (Hall, 2006). The research highlights body archives that encourage interpretative multiplicity and creative interaction, as in the Bottle Duets project, which performs an open invitation to resignify memories and experiences through dialogue with a collective and open becoming.